Costantinopoli: il fato di una città. L’antica Bisanzio, città di Costantino, capitale dell’Impero Romano d’Oriente. Il suo ruolo dopo la caduta in mano turca - Parlato, Vittorio (Cultura giuridica e diritto vivente, 2018)
[Costantinopoli: the fate of a city] The ancient Byzantium, city of Constantine, capital of the Eastern Roman Empire and its primacy over the churches of the East. His civil and ecclesiastical role after the fall in Turkish hands as bearer and continuator, albeit in different ways, of Byzantine civilization, in the Slavic world and also in the West.